Társadalmi folyamatok Budapest közigazgatási határának két oldalán - Izsák, Éva (Tér és Társadalom, 1996)
In accordance with Act XXVI of 1949, 23 settlements (7 towns and 16 villages) were joined up with the area of Budapest. Having lost the independence of self goverment, these settlements started to develop along a completely new course, as a consequence of wich they have become an integral part of the capital over the past decades. At the same time, due to the local goverment reforms of 1950, 25 settlements (4 towns and 21 villages) became immediate neighbours of the capital. Along both sides of the current local goverment boundaries, an unusual zone can be found. The inner parts consist of areas which before 1950 were independent and lay in in the shadow of the capital, whereas today they constitute whole districts or parts of districts of the capital itself. On the other side of the border the settlements are in a similar situation to those that were independent before 1950. Surveys of settlements are usually adapted to local goverment boundaries. A boundary on the other hand is not on every case a dividing line, it often links neighbouring areas. The survey of the capital's border settlements and the presentation of the dividing and joining qualities of the boundaries is also necessary in the study of the capital's agglomeration. The three "model" areas (the north-west, north east and south east) have been demonstrating diverse trends of development in the various social and socio-geographic tendencies adapt to boundaries. Is the local goverment boundary a real "living" boundary, and do the individual social patterns adapt to artificial frontiers?